Beckman Model 3600 Recording UV/Visible Spectrophotometer (1960)
This model followed in the tradition of the DU, the first ultraviolent/visible spectrum spectrophotometer. The first Beckman Instruments DU Spectrophotometer was developed in 1940, when the company was still called National Technical Laboratories. Spurred by employee Howard Cary (who had previously been involved in pH meter development), NTL produced its first DU Spectrophotometer prototype in 1940. This first Model A contained a glass prism, while subsequent models used quartz crystal. The DU was initially developed under a U.S. government contract, but was ultimately used in many important scientific discoveries and developments of the 20th century, including penicillin and synthetic rubber research, petroleum refining, and the creation of explosives.
Keywords: Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Optical spectroscopy; Beckman Instruments, Inc.